Queen's Royal College, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Exterior view of the Queen’s Royal College in Port of Spain, Trinidad. This is a secondary school that admits male students only. The Queen's Park Savannah lies opposite to the school and three people can be seen huddled on a bench there. Postcard number 77764.
Colour: Red, Green, Blue and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; 1952; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Fences--Trinidad and Tobago; Benches--Trinidad and Tobago; Trees--Trinidad and Tobago; Tower clocks--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)